Association between cigarette-smoking and prevalence of oral mucosal lesions among malaysian army personnel - Zain, R.B.; Razak, I.A. (Blackwell Publishing, 1989)
The association between cigarette smoking and the prevalence of oral mucosal lesions was examined in 495 Malaysian army personnel. No associations between cigarette smoking and recurrent aphthous ulcerations, pre-leukoplakia and frictional keratosis could be obtained in this study. Positive associations were found between cigarette smoking and leukoedema as well as denture stomatitis. There was a negative association between cigarette smoking and the presence of coated tongue.